Gastric Xanthoma Associated with Gastric Cancer Development: An Updated Review - Faycal Awaleh Moumin; Abdimajid Ahmed Mohamed; Abdirahman Ahmed Osman; Jianting Cai (Canadian Journal of Gastroenterology and Hepatology)
Gastric xanthelasma (GX) is a rare tumor-like lesion customarily found as an incidental finding due to its asymptomatic appearance. Grossly, it is a well-marked yellow-white plaque created in the lamina propria by microscopic clusters of foamy macrophages. Xanthelasma is rarely correlated with gastric hyperplastic polyps; gastric xanthomas are rare benign lesions that appear to be associated with inflammation of the gastric mucosa. Etiopathogenesis is also unclear, but it has been suggested to be involved in chronic gastritis, infection with Helicobacter pylori (H. pylori), diabetes mellitus, and hyperlipidemia. The gastric xanthoma prevalence ranges from 0.23% to 7%. Orth first described the condition in 1887. It has been found that xanthelasmas are associated with chronic gastritis, gastrointestinal anastomosis, intestinal metaplasia, and H. pylori infection. These lesions predispose patients to gastric cancer conditions. Xanthoma (GX) was reported to be a predictive marker for early gastric cancer. However, the effectiveness of these scores and xanthoma (GX) as predictive markers for early gastric cancer detected after H. pylori eradication remains unknown.